Answer:
a^3-b^3
Step-by-step explanation:
(a−b)(a2+ab+b2)
=(a+−b)(a2+ab+b2)
=(a)(a2)+(a)(ab)+(a)(b2)+(−b)(a2)+(−b)(ab)+(−b)(b2)
=a3+a2b+ab2−a2b−ab2−b3
=a3−b3
Answer:
10 or x=10
Step-by-step explanation:
First we can combine like-terms.
8x+6=86
Then subtract 6 from both sides
8x=80
Divide by 8
x=10
Answer:
x= - 8
Step-by-step explanation:
multiply both sides by 4 to get rid of the fractions. you should then get:
2x-4x=x+24
then get all the x terms to one side by subtracting by x on each side:
2x-4x-x=24
then simplify:
-3x=24
divide by -3 on each side:
x= - 8
The square root of 80 can be broken up into the square root of 16 x square root of 5. We know that the square root of 16 is 4. So in the form (a sqrt b)
A would be 4 and b would be 5.
Answer: 4 sqrt 5